Chronic Toxicity Study For Tamra Bhasma (A Generic Ayurvedic Mineral Formulation) in Laboratory Animals - V.D. Sangle, M.K. Vahalia*, K.S. Thakur S. Nadkarni, (Recent Research in Science and Technology, 2011)
Tamra Bhasma – a generic Ayurvedic mineral formulation was studied for its toxicity in laboratory animals. Chronic toxicity was conducted in albino rats (wistar strain). In this study Tamra Bhasma was administered orally, daily to different groups of albino rats in TD (Tamra Bhasma) and 2 TD (Tamra Bhasma 2 x Therapeutic Doses) doses for 3 months. Tamra Bhasma was found to be relatively safe at these dose levels. There was no mortality. No significant behavioural changes were noted in any of the group studied. No major alterations were observed in haematology, serum biochemical, necropsy and histopathology at the administered dose level. The overall chronic toxicity study data indicates that the test substance at its TD and 2TD level is very well tolerated since no toxicity symptoms of serious cause could be observed in any of the parameters analysed.